2014
DOI: 10.4028/www.scientific.net/amr.966-967.521
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Al/Mg-Hybrid-Joints by Ultrasound Supported Friction Stir Welding - Mechanical Properties, Microstructure and Corrosion Behavior

Abstract: Fusion welding of dissimilar metals is in the most cases difficult or even impossible as a result of different melting points and the development of undesirable brittle intermetallic phases. This often leads to joint strengths considerable below the tensile strength of the base materials. By using Friction Stir Welding (FSW) it is possible to reduce the development of the intermetallic phases of Al/Mg-joints significantly but not to avoid them completely. Hence a hybrid welding system at the WKK of the Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 16 publications
(27 reference statements)
4
8
0
2
Order By: Relevance
“…With the increase of ultrasound power the intensity of stirring in the nugget increases. This correlates with investigations stating a better stirring by the introduction of ultrasound [24]. If the ultrasound is introduced from the aluminum side the magnesium/nugget interface is much more inclined compared to the interface of the friction stir welding joint.…”
Section: Light Microscopic Investigationssupporting
confidence: 81%
“…With the increase of ultrasound power the intensity of stirring in the nugget increases. This correlates with investigations stating a better stirring by the introduction of ultrasound [24]. If the ultrasound is introduced from the aluminum side the magnesium/nugget interface is much more inclined compared to the interface of the friction stir welding joint.…”
Section: Light Microscopic Investigationssupporting
confidence: 81%
“…These findings were likewise proven by Tarasov et al, who found the same grain size reduction as well as a reduction of tensile stress in the welding direction for FSW joints of AA7475 realized by ultrasonic vibration assisted friction stir welding at which the power ultrasound got transmitted into the metal sheets by the backing plate [27]. As mentioned before for Al/Cu joints the transmission of power ultrasound in parallel to the FSW process is beneficial for dissimilar metal joints, which is verified by the investigations of Strass et al for Al/Mg joints and Thomä et al for Al/St joints who used the approach of ultrasound enhanced friction stir welding leading to improved quasistatic and cyclic properties amongst other findings [22,28]. Beside all these different approaches for hybrid ultrasound assisted friction stir welding processes showing positive influence of the power of ultrasound for similar as well as dissimilar metal joints, there is still a lack of knowledge regarding the impact of the ultrasonic oscillation in detail.…”
Section: Introductionsupporting
confidence: 55%
“…Each of these three hybrid FSW processes are based on the additional heating of the joining partners, that seemed to be beneficial so far in the combination with optimized friction stir welding parameters but included the risk of a more pronounced growth of grains for similar metal joints or IMP for dissimilar metal joints. Therefore, the power ultrasound assisted FSW approach seems to be most promising due to the mechanical energy input caused by the ultrasound oscillation, which interacts in-process with oxides, developing and/or existing intermetallic phases and potentially breaking them up leading to higher monotonic and cyclic strengths [22]. Furthermore, the material flow can be increased, and the process forces can be reduced [23].…”
Section: Introductionmentioning
confidence: 99%
“…The improved stirring of dissimilar aluminum and magnesium cast alloys by ultrasound enhancement resulted in a more pronounced corrosive attack of the nugget, whereas the application of the USE-FSW process on AA6061/ SAE1006 joints showed no significant changes in the corrosion properties. [19][20][21][22] In addition, an accelerated corrosion of the magnesium alloy in a chloride-containing electrolyte was found when it was measured in contact with the nugget area. [19][20][21] The current work investigates the influence of ultrasound with varying power input on the corrosion properties of dissimilar AA6061/DP600 joints in comparison to the conventional FSW process and how they are correlated with the microstructure of the joints.…”
Section: Introductionmentioning
confidence: 99%